2022
DOI: 10.2147/opth.s350029
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanics for Ocular Hypertension, Primary Open-Angle Glaucoma, and Amyloidotic Glaucoma: A Comparative Study by Corvis ST

Abstract: Background To evaluate biomechanical parameters of the cornea provided by Corvis ST in patients with ocular hypertension, primary open-angle glaucoma, and amyloidotic glaucoma and to compare with healthy controls. Methods This was a cross-sectional study of patients with ocular hypertension, primary open-angle glaucoma, and amyloidotic glaucoma that underwent Corvis ST imaging. Primary outcome was the comparison of corneal biomechanical parameters between study groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Some reported corneas of POAG were less deformable compared to controls, 17 , 29 whereas others reported that no biomechanical differences were found between the two groups. 30 , 31 The possible reasons for this disagreement could be due to the influences of antiglaucoma medications on corneal biomechanics, differences in sample size and variables used for adjustment. When NTG and HTG were analyzed separately and compared with controls ( Table 2 ), DA, AT1 and HC time showed similar changes in the two glaucoma groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some reported corneas of POAG were less deformable compared to controls, 17 , 29 whereas others reported that no biomechanical differences were found between the two groups. 30 , 31 The possible reasons for this disagreement could be due to the influences of antiglaucoma medications on corneal biomechanics, differences in sample size and variables used for adjustment. When NTG and HTG were analyzed separately and compared with controls ( Table 2 ), DA, AT1 and HC time showed similar changes in the two glaucoma groups.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen of the 31 articles used ORA to investigate differences in corneal biomechanical parameters between glaucoma patients and normal controls, 10,14,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] while 15 used CST. 11,16,36,37,[40][41][42][43][44][45][46][47][48][49][50] The procedure of the literature search and the reasons for exclusion are shown in Fig. 1.…”
Section: Characteristics Of the Studies Included In The Meta-analysismentioning
confidence: 99%
“…[11][12][13] Otherwise, several studies have suggested that patients with ocular hypertension (OHT) but no glaucomatous changes showed less deformable corneas. 9,10,[14][15][16] These corneal biomechanical differences indicate that the appearance and progression of glaucoma could be associated with specific corneal biomechanical DOI: 10.1097/IJG.0000000000002170 changes, 17,18 which may offer a novel perspective on glaucoma pathology.…”
mentioning
confidence: 99%
“…Thus, SSI could be suitable for the assessment of reduction in corneal stiffness in the natural progression of keratoconus and help recognize potential keratoconic eyes ( Padmanabhan et al, 2022 ; Liu et al, 2021a ). Some studies reported correlations between SSI values and IOP; therefore, SSI values may also be used for the differentiation of glaucoma types ( Ye et al, 2021 ; Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%